1997
DOI: 10.1159/000190228
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Study of Glomerular Capillary Loops at Different Perf usion Pressures as Revealed by Quick-Freezing, Freeze-Substitution and Conventional Fixation Methods

Abstract: Wistar rat kidneys were perfused with some fixatives at different pressures of 100, 150, 200 or 250 cm H20 via the aorta and were studied by the quick-freezing and freeze-substitution (QF-FS) or deep-etching (QF-DE) methods, in addition to the conventional immersion or perfusion fixation method. Different parts of glomerular capillary walls were selected for morphometric analyses. It was demonstrated that the widths of glomerular slit diaphragms and the spaces between foot processes were more widely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
3
11
0
1
Order By: Relevance
“…3), typical three-layered structures of GBM were observed under each perfusion pressure condition, as previously reported [19]. Moreover, the widths of the LRE and LRI were thicker than those seen by the QF-DE method (fig.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…3), typical three-layered structures of GBM were observed under each perfusion pressure condition, as previously reported [19]. Moreover, the widths of the LRE and LRI were thicker than those seen by the QF-DE method (fig.…”
Section: Resultssupporting
confidence: 85%
“…The ultrastructures of glomerular capillary walls were gradually changed at different perfusion pressures, as reported before [19]. By the QF-DE method for pure morphology, filamentous structures in the GBM were observed more clearly than those seen on the ultrathin sections (fig.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The actual slit diaphragm is considered to be a rather rigid structure. However, it has recently been suggested that at least the slit area might increase with increasing perfusion pressures of the glomerulus (34,35). Because the actual molecular structure of the slit diaphragm is, as yet, unresolved, it is premature to speculate on a molecular assembly allowing change in the width of the slit.…”
Section: Discussionmentioning
confidence: 99%